Procedures for translating English procurement terminologies into Vietnamese = Phương thức dịch thuật ngữ Tiếng Anh trong đấu thầu sang Tiếng Việt - Bùi, Thị Như (2021)
This paper tries to shed some light on English-Vietnamese translation of procurement terminologies in relating documents such as procurement documents, procurement guidelines by Asian Development Bank and Vietnam's Law on procurement issued in 2005 by the Government of Vietnam. The study first gives theoretical background about translation including its definition, translation procedures and definition of terminology. The main goal of this study is to find out the common translation procedures applied in translating English procurement terms into Vietnamese and what is the most dominant one. Besides, this paper also goes further into definition and character of terminologies and procurement to give background knowledge about these ones before having deeper analysis about procurement terminologies. Both qualitative and quantitative methods are applied in this study. The result points out that there are five translation procedures including borrowing, calque, transposition, equivalence and modulation are applied in Vietnamese-English translation of procurement terminologies and transposition is the most dominant procedure. A detail investigation and analysis about English-Vietnamese translation procedures of procurement terminologies and suggestions for each of translation procedures have been carried out. Although there is some limitations remaining in this study, researcher hopes that findings of the study can be helpful for students, translators and others relating to procurement fields.